A theory-based behavior-change intervention to reduce alcohol consumption in undergraduate students: Trial protocol Health behavior, health promotion and society - Hagger, Martin; Wong, G.; Davey, S. (BioMed Central Ltd., 2015)
Background: Excessive alcohol consumption on single occasions among undergraduate students is a major health issue as research has shown this pattern of drinking to be related to maladaptive health and psychosocial outcomes. Brief, theory-based interventions targeting motivation and self-control as behavior-change techniques have been identified as effective means to reduce alcohol consumption, but few studies have examined the interactive effects of these components. The aim of the present study is to develop a brief theory-based intervention using motivational and self-control intervention techniques to reduce alcohol consumption in undergraduate students. Methods/Design: The intervention will adopt a factorial design to test the main and interactive effects of the techniques on alcohol consumption. Using mental simulations and the strength model of self-control as the theoretical bases of the intervention, the study will adopt a fully randomized 2 (mental simulation: mental simulation vs. control irrelevant visualization exercise) × 2 (self-control training: challenging Stroop task vs. easy Stroop task) between-participants design. Non-abstinent undergraduate students aged 18 years or older will be eligible to participate in the study. Participants will complete an initial survey including self-reported alcohol consumption measures, measures of motivation and self- measures. Participants will be randomly allocated to receive either a mental simulation exercise presented in print format or a control irrelevant visualization exercise. Thereafter, participants will be randomly assigned to receive a challenging online self-control training exercise or an easy training exercise that has little self-control demand over the course of the next four weeks. Four weeks later participants will complete a follow-up alcohol consumption, motivation and self-control measures. Discussion: This study will provide the first evidence for the individual and interactive effects of motivational and self-control training techniques in an intervention to reduce alcohol consumption. It will also demonstrate the importance of adopting multiple theoretical perspectives and a factorial design to identify the unique and interactive impact of behavior-change techniques on health behavior. Trial registration: The trial is registered with the Australian and New Zealand Clinical Trials Registry, ACTRN12613000573752.